Motion Onset Captures Attention - Abrams, Richard A.; Christ, Shawn E. (Psychological Science, 2003)
Although visual motion may seem salient, motion per se does not automatically attract attention. We show here, however, that the onset of motion does indeed attract attention. In three experiments, subjects identified target letters in displays that contained targets and distractors. There was no advantage for moving letters among static ones, but there was an advantage for objects that had recently started to move despite the fact that the motion was uninformative. If some additional time was allowed to elapse after motion onset, inhibition of return slowed responding to the item that had started to move—a further sign that the motion onset had captured attention. Finally, detection of target letters was found to be independent of the number of distractors in the display if the target had undergone motion onset, also indicative of attentional capture. We discuss the adaptive significance of sensitivity to onsets in the presence of a relative insensitivity to ongoing motion.